Hubungan Kewenangan antara Kepala Daerah dengan DPRD dalam Sistem Pemerintahan Daerah Perspektif Siyāsah Syar’iyyah - Noranisa (Sosiosaintika, 2026)
This study aims to examine the relationship of authority between Regional Heads and Regional People’s Representative Councils (DPRD) within the framework of regional governance and to analyze it from the perspective of Siyāsah Syar’iyyah. This research applies a normative legal method using statutory, conceptual, and Islamic law approaches. The results of the study show that, normatively, the relationship between Regional Heads and DPRD is a partnership based on the principle of checks and balances, in which the DPRD carries out legislative, budgeting, and supervisory functions, while the Regional Head performs executive functions. However, in practice, this relationship is often influenced by political conflicts, institutional disharmony, and abuse of authority, which hinder the implementation of regional governance. From the perspective of siyāsah syar’iyyah, such a relationship should be based on the principles of deliberation (shura), justice, trustworthiness (amānah), and supervision (ḥisbah) in order to realize public welfare. Therefore, strengthening integrity, political ethics, and commitment to the values of justice and public benefit is essential in the administration of regional government to achieve good governance.